Alcaloides e sesquiterpenoides de anaxagorea dolichocarpa: isolamento, caracterização estrutural e citotoxicidade - Sales, Kaio Aragão (2020)
In Brazil, the most biodiverse country in all around the world, the medicinal use of plants is a usual practice. The Annonaceae family, with around 2,400 species, contributes significantly to the diversity in Neotropical forests, besides being used in the diet and traditional medicine, due to its edible fruits and therapeutic properties. From one of its species, the Anaxagorea dolichocarpa, popularly known as envira and widely distributed in the neotropical region, identification of alkaloids and terpenoids were published, along in vitro antitumor activities reports. Thus, this work pursuit to expand the knowledge about this specie, through phytochemical and cytotoxic activity investigation. For this, the plant material was collected in Cruz do Espírito Santo-PB and subjected to processes of extraction, purification and analysis of chemical constituents. These procedures were carried out by classical laboratory methods as well as modern techniques of HPLC, NMR, MS and Circular Dichroism. Thus, from the roots extracts of the plant, it was possible to isolate and characterize the chemical structures of six alkaloids, the two new compounds dolichocarpine and 9- methoxyeupolauramine, in addition to the well-known eupolauramine, 3- methoxyeupolauridine, eupolauridine and 4-methylsampangine, and also six unprecedented humulene-type sesquiterpenoids, called dolichocarpols A-F. Of these, five alkaloids and three sesquiterpenoids had their cytotoxic activity investigated against HCT-116 (human colorectal carcinoma cells), with up to 32.42% inhibition for 3-methoxyupolauridine, and L929 (murine non-tumor fibroblasts cells), with 30.76% inhibition for dolichocarpol F. Therefore, the results obtained by this study contribute to the chemical and biological activity of A. dolichocarpa knowledge.